Karakteristik Ikan Pelagis Kecil Yang Dipasarkan Di Pasar Arumbai, Kota Ambon - Rahayu Ode; Alberth Ch. Nanlohy; Kedswin G. Hehanussa; Julian Tuhumury; Friesland Tuapetel (Universitas Pattimura, 2023)
Small pelagic fish play a crucial role in the marine food chain and have significant economic value, yet information about them remains scarce. This research aims to map the origin and characteristics of small pelagic fish marketed at Arumbai Market in Ambon City. The study was conducted over six months, from May to October 2023, at Arumbai Market. The research utilized survey methods and interviews, and the data were analyzed descriptively. Observations were made on the quantity and size structure of four dominant fish species from five different fish landing locations: Hila, Tulehu, Laha, Hitu, and Latuhalat. The results of this research revealed variations in the composition of dominant small pelagic fish species sold, from the highest to the lowest, namely Decapterus sp, Rastreligger sp, Selar sp, and Auxis sp. The contribution of the five fish landing locations is as follows: Hila (31%), Hitu (24%), Tulehu (18%), Laha (15%), and Latuhalat (12%). Differences in the composition of the quantity and size marketed are suspected to be due to variations in seasons, fishing tools, and capture areas.